Does Digital Media Literacy Influence Students’ Perception of Hoax? - Primardiana Hermilia Wijayati; Nur Octavi Mandasari; Rizman Usman (Universitas Nahdlatul Ulama Blitar, 2021)
The purpose of this study was to find out whether there was the significant relationship between digital media literacy and students' perception of hoax. This research uses descriptive correlation methods with surveys as data collection. Respondents in this study were students of diploma, undergraduate, and graduate from 18 study programs at the Faculty of Letters, Universitas Negeri Malang. This study uses surveys conducted online using the Google Form website. The data were then analyzed by using Pearson’s Product Moment Correlation in SPSS software. The results showed that there was a significant relationship between the level of digital media literacy and the perception of hoaxes, and it was in the moderate correlation. Based on the review of related literature, moderate correlation was occur due to several factors such as biased thinking, easily provoked age group, and difficulties in finding accurate media agencies.